THE EFFECT OF SCHOOL ENVIRONMENT ON ACHIEVEMENT MOTIVATION AMONG HIGH SCHOOL STUDENTS IN ISRAEL - Gadir, Hulud (E-Journal VFU, 2025)
The school environment is a crucial factor in shaping students’ motivation to achieve academic achievement, as it directly affects students’ academic performance and psychological well-being. This study aims to explore the influence of the physical, social, and psychological elements of the school environment on achievement motivation among high school students in Israel. A descriptive approach was used based on a questionnaire distributed to a sample of 150 randomly selected students. The results show that the relationships between teachers and students, the physical organization of school facilities, and the use of modern technology are among the most prominent factors influencing students’ motivation. The study recommends promoting positive interaction between students and teachers and developing school infrastructure to provide a stimulating learning environment.